Agricultural economics and distribution effects: Presidential Address to the 25th Conference of the International Association of Agricultural Economists, August 16-22, 2003, Durban, South Africa - von Braun, Joachim (2003)
In this address, I highlight the large and growing national and international inequalities related to agriculture and rural areas, which threaten peace, growth, and sustainable development; I argue that we ought to rethink the nature and implications of distributional effects in agriculture and rural areas; I argue for moving from partial to more holistic thinking about distributional effects, and offer suggestions on what to do about them. -- from text.